De Anima: Or, Ulysses and the Theological Turn in Modernist Studies - David Ayers (Humanities, 2017)
Focusing on Joyce’s use of Aristotle’s De Anima, and on Aquinas’s response to Aristotle, this essay takes, as its starting point, the recourse to two areas of enquiry in recent work on modernism: animal studies and phenomenology. In this essay we examine the intersection within Ulysses of the concept of the soul in Aristotle and Aquinas, show how this relates to questions of animality, and open the way to asking what implication the theological reflection on the soul at the centre of Ulysses might have for a process of uncovering theological contents in the concept of “life” in modernist studies more generally.